Love Without Limits : Jesus' Radical Vision for Love with No Exceptions - Bussie, Jacqueline Aileen (Book collections on Project MUSE., 2018)
The love of God crosses all boundaries. Every. Single. One. Every day, millions of people lament the loss of civility, respect, and hope, and they wonder if it's possible to cultivate a love big enough to overthrow hate and heal our hurts. With courage, authenticity, and relevance, Jacqueline A. Bussie proclaims, "Yes! It's possible!" and urges readers to widen love's wingspan and to love as God loves--without limits or exceptions. In Love Without Limits, Bussie imparts practical solutions for people of faith who yearn to love across division and difference in these troubled times. Through poignant personal memoir, engaging theological reflection, inspiring true stories of boundary-busting friendships, creative readings of scripture, and surprising shout-outs to some of love's unsung heroes, Bussie challenges readers to answer God's call to practice a love so deep, it subverts the social order; so radical, it scandalizes the powerful; so vast, it excludes no one.